POLITICAL IMAGE CONSTRUCTION OF FEMALE ARTIST POLITICIANS IN ONLINE MEDIA FRAMING - Berthanila, Rethorika; Santi, Endang Tri; Marthalena, Marthalena; Perbawani, Pulung S. (ASPIRATION Journal, 2024)
The political image of female politicians and artists on the political stage is still a hot and interesting topic of discussion in society. Many people still believe that celebrity politicians, especially women, only rely on popularity to win and be elected as members of the House of Representatives. It is not only limited to that, the participation of female artist politicians could be based on government policy regarding a 30% quota, or it could also be due to political education and the influence of technology that has encouraged female artists to be present in the political field. However, negative images and assumptions still prevail due to the construction of artists being chosen just because they are popular to gain votes. Therefore, this research aims to see how the media frames news so that it can construct the audience's thoughts about the political image of female politicians and artists. This research uses a qualitative method using Robert M. Entman's framing analysis approach, where the analysis uses four elements which have become the basis for analysis to dissect how Kompas.com and Tempo. co media frame news. The results of this research show that the political image of female celebrity politicians as members of the House of Representatives still lacks trust from the public. This cannot be separated from the fact that the highlighted news does not cover much about their performance as members of the People's Representative Council, but more about their style and style. their lives as artists. Therefore, the suggestions and recommendations recommended are that, apart from politicians, artists must continue to show consistent performance as members of the people's representatives, they must also be supported by media reports which must highlight their performance, professionalism and abilities as politicians. In this way, the image of artist politicians in society can change to be more trusting and supportive of the role of artists in government. Furthermore, the researcher hopes that this scientific work can provide scientific development and contribute to efforts to build a good political climate.